1990
DOI: 10.1007/bf01316322
|View full text |Cite
|
Sign up to set email alerts
|

Bud formation and metamorphosis inCassiopea andromeda (Cnidaria: Scyphozoa): A developmental and ultrastructural study

Abstract: Abstract.Asexual reproduction by formation of swimming buds which metamorphose directly into polyps plays a most important role in the propagation of Cassiopea andromeda (Cnidaria: Scyphozoa). (C. andromeda polyps, originally supplied by the LSbbecke Museum and Aquarium Dtisseldorf, FRG, were cultured in our laboratories.) We have defined five budding stages and investigated epithelial recruitment and dynamics during bud formation using intracellular vital stains. The region of cell recruitment was found to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…Pardy & Muscatine (1973) have demonstrated that during the reestablishment of the symbiosis between aposymbiotic green hydra and Chlorella, the algae are taken in by phagocytosis of gastrodermal cells. Hofmann & Honegger (1990) have shown that zooxanthellae are occasionally found in the swimming buds of Cassiopeia andromeda. The microalgae are located within the mesoglea or between the bases of the endodermal ceils.…”
Section: Discussionmentioning
confidence: 99%
“…Pardy & Muscatine (1973) have demonstrated that during the reestablishment of the symbiosis between aposymbiotic green hydra and Chlorella, the algae are taken in by phagocytosis of gastrodermal cells. Hofmann & Honegger (1990) have shown that zooxanthellae are occasionally found in the swimming buds of Cassiopeia andromeda. The microalgae are located within the mesoglea or between the bases of the endodermal ceils.…”
Section: Discussionmentioning
confidence: 99%
“…The polyps that release the ephyrae should be cultured in a separate tank with an optional catch basin. The attached polyp of Cassiopea spp will release freeswimming buds that metamorphose into new polyps (Hofmann & Honegger, 1990). The polyps should be kept separate from the grow-out system otherwise they may colonize it and polyps are able to sting the medusae they propagate (Sommer, 1992).…”
Section: Methodsmentioning
confidence: 99%
“…The medusa lays with its umbrella surface (exumbrella) toward the ground, while the oral arms are stretched into the water column to catch zooplanktonic prey. This also provides the endosymbiotic zooxanthellae (dinoflagellates of the species Symbiodinium microadriaticum Freudenthal, 1962) that can be found in the epithelial layer of the animal with sunlight and in turn contribute photosynthates to the jellyfish (Rahat and Adar 1980;Hofmann and Kremer 1981;Hofmann and Honegger 1990;Hofmann et al 1996).…”
Section: Introductionmentioning
confidence: 95%
“…After fertilization, eggs develop into planula larvae in the center of the female's oral disc (Gohar and Eisawy 1960;Hofmann et al 1996). Released planulae settle on hard substrates and develop into asexually reproducing polyps that show two typical modes of asexual reproduction: (1) the formation of swimming buds metamorphosing into additional polyps after settlement and (2) monodisc strobilation, during which the upper polyp body undergoes transverse fission releasing a single juvenile medusa, called an ephyra (Hofmann et al 1978;Hofmann and Honegger 1990;Hofmann and Gottlieb 1991).…”
Section: Introductionmentioning
confidence: 99%